Graphene and visible light enhance pyrite-based Cr(VI) reduction in the presence of Acidithiobacillus ferrooxidans. (February 2019) - Gan, Min; He, Peng; Gu, Chunyao; Zheng, Zhihe; Zhu, Jianyu; Zhou, Shuang; Liu, Xinxing; Qiu, Guanzhou
Abstract: Hexavalent chromium pollution has attracted increasing attention due to the toxic effect on living organisms. Cr(VI) reduction based on natural pyrite is a sustainable and economical choice for efficient Cr(VI) remediation, while the passivation effect usually limits its application. In this study, the catalytic effects of graphene and visible light in pyrite-based Cr(VI) reduction were systematically investigated. Monosulfide was oxidized to disulfide by A. ferrooxidans, thus driving pyrite dissolution and reactive sites regeneration. The reduction efficiency of the light-graphene-biotic system was 1.27 and 2.9 times higher than that in the dark biotic and dark abiotic system. Synergistic effect on Cr(VI) reduction existed in both chemical and biotic system. Graphene played a dominant role in the catalytic process compared with visible light. The promotion effect increased under the graphene load. Graphene, as the reservoir of free ions, provided reactive sites for secondary iron mineral formation and relieved the passivation effect. In addition, as a redox mediator, it accelerated intermediate sulfur species oxidation by A. ferrooxidans, which enhancedthe dissolution of sulfide mineral and the redox conversion of Cr(VI). Graphene promoted the regeneration of reactive sites on pyrite, thus enhancing Cr(VI) reduction efficiency. Graphical abstract: Highlights: Passivation effect on pyrite relieved under the activity of A. ferrooxidans. Synergistic effect promoted pyrite dissolution and Cr(VI) reduction. Graphene acted as redox mediator and reservoir of free ions in reduction. Graphene promoted A. ferrooxidans, oxidization on intermediate sulfur species.